Duty : memoirs of a Secretary at war - Gates, Robert Michael, 1943- (Alfred A. Knopf, 2014)
The former Secretary of Defense offers a candid account of serving Presidents George W. Bush and Barack Obama during the wars in Iraq and Afghanistan.